The moderating effect of moral licensing on religiosity and charity donations - Sanghani, Rohan (2022)
The impact of Covid-19 has been felt on a global scale, with several industries, including charities facing severe setbacks as a result of the pandemic. In Malaysia, for example, charities are facing financial struggles to meet the needs of the underprivileged. Above that, global unemployment rates have witnessed a sharp increase. This means that more and more people may not be able to afford to donate to charity.